2004
DOI: 10.1643/cg-04-106
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA and Color Pattern Variation in Three Western Atlantic Halichoeres (Labridae), with the Revalidation of Two Species

Abstract: Genetic surveys of widely distributed marine species often find previously undetected biodiversity. In the present study, populations of three species of Halichoeres were sampled across their entire geographical ranges: Halichoeres cyanocephalus and Halichoeres maculipinna were sampled on both sides of the Amazon freshwater outflow, the main biogeographic barrier in the tropical western Atlantic; and Halichoeres garnoti was sampled in the Caribbean and Bermuda. Genetic divergences between populations separated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
2
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 34 publications
6
66
2
1
Order By: Relevance
“…These two populations are separated by the 2300 km wide Amazon river barrier. Even though their divergence is smaller than that of some surgeonfishes and wrasses influenced by the same barrier (Rocha et al, 2002(Rocha et al, , 2005Rocha, 2004) and there is no difference in morphology or the nuclear genes analyzed, their genetic uniqueness at the mtDNA supports the view that these populations should be regarded as distinct evolutionary units and not as a single, widely distributed panmictic species, and be managed accordingly (Rocha et al, 2007).…”
Section: Morphology Versus Moleculesmentioning
confidence: 74%
“…These two populations are separated by the 2300 km wide Amazon river barrier. Even though their divergence is smaller than that of some surgeonfishes and wrasses influenced by the same barrier (Rocha et al, 2002(Rocha et al, , 2005Rocha, 2004) and there is no difference in morphology or the nuclear genes analyzed, their genetic uniqueness at the mtDNA supports the view that these populations should be regarded as distinct evolutionary units and not as a single, widely distributed panmictic species, and be managed accordingly (Rocha et al, 2007).…”
Section: Morphology Versus Moleculesmentioning
confidence: 74%
“…This procedure was based on recent reports about biogeography of Brazilian reef species (Floeter and Gasparini, 2000;Floeter et al, 2001;Rocha, 2004;Ferreira et al, 2004). According to these authors, the Brazilian coastal zones can be reliably separated into northeastern, southeastern, and oceanic islands.…”
Section: Study Area and Sampling Collectionmentioning
confidence: 99%
“…Recent phylogeographic studies have revealed cryptic diversity within species [9] and the influence of porous hydrological barriers [10]. Each study has provided valuable insights, yet an overview of the role of barriers is lacking.…”
Section: Introductionmentioning
confidence: 99%